Muscular and arm crawl stroke power: evaluating their relationship - Dominguez-Castells, R.; Arellano, R. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to determine the relationships between dry-land power, swimming power delivered to an external weight and swimming performance. 18 swimmers performed 4 tests: 1RM bench press, 25m sprint velocity, bench press power and swimming power (both are relative to body mass power). Maximal bench press power was 5.41W/kg and it was obtained with 41.32%RM and a barbell velocity of 1.04m/s. Maximal arm crawl stroke power was 0.86W/kg and was developed with 47.07% of maximal load and a swimming velocity of 0.75m/s. A moderate relationship of r=0.538 (p<0.05) was found between bench press power and swimming power. There was a higher correlation between swimming power and sprint velocity (r=0.762, p<0.01).